2018
DOI: 10.24059/olj.v22i1.995
|View full text |Cite
|
Sign up to set email alerts
|

Computer Science Students’ Attitudes Towards the Use of Structured and Unstructured Discussion Forums in Fully Online Courses

Abstract: This study aims to investigate and analyze the attitudes and opinions of computer science students at two academic colleges of Education with regards to the use of structured and unstructured discussion forums in computer science courses conducted entirely online. Fifty-two students participated in two online courses. The students in each course were divided into two groups: the experimental group, which participated in the structured discussion forum, and the control group, which participated in the unstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
(27 reference statements)
1
14
1
1
Order By: Relevance
“…This was the second most studied theme under engagement. Researchers examined increasing interpersonal interactions ( Cung et al, 2018 ), learner-learner interactions ( Phirangee, 2016 ; Shackelford & Maxwell, 2012 ; Tawfik et al, 2018 ), peer-peer interaction ( Comer et al, 2014 ), learner-instructor interaction ( Kuo et al, 2014 ), learner-content interaction ( Zimmerman, 2012 ), interaction through peer mentoring ( Ruane & Koku, 2014 ), interaction and community building ( Thormann & Fidalgo, 2014 ), and interaction in discussions ( Ruane & Lee, 2016 ; Tibi, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…This was the second most studied theme under engagement. Researchers examined increasing interpersonal interactions ( Cung et al, 2018 ), learner-learner interactions ( Phirangee, 2016 ; Shackelford & Maxwell, 2012 ; Tawfik et al, 2018 ), peer-peer interaction ( Comer et al, 2014 ), learner-instructor interaction ( Kuo et al, 2014 ), learner-content interaction ( Zimmerman, 2012 ), interaction through peer mentoring ( Ruane & Koku, 2014 ), interaction and community building ( Thormann & Fidalgo, 2014 ), and interaction in discussions ( Ruane & Lee, 2016 ; Tibi, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Salter and Conneely (2015) found that while both structured and unstructured discussion forums were viewed positively by students, structured discussion forums were found to be more engaging. Tibi (2018) found that students had a more positive attitude toward a structured discussion forum compared with an unstructured discussion forum.…”
Section: Discussionmentioning
confidence: 91%
“…For example, student participation and engagement were found to improve when the discussion forum imposed a specific interaction pattern on the submission of posts (Wegmann & McCauley, 2014). Other studies have examined the impact of both process and structure of discussion forums on variables such as cognitive presence (Chen et al., 2019), attitude toward discussion forum usage (Tibi, 2018), student perception of positive impact and phases of knowledge construction (Gao, 2014; Howell et al., 2014), and the development of critical thinking skills (Greenlaw & DeLoach, 2003). Akcaoglu and Lee (2016) studied the effect of group size in an online forum on sociability, social space, and group cohesion.…”
Section: Background Literaturementioning
confidence: 99%
“…Los avances de las tecnologías de la información y comunicación (TIC) están provocando que las instituciones educativas actualicen los modelos pedagógicos y las estrategias didácticas, con la finalidad de mejorar la asimilación del conocimiento y el desarrollo de las habilidades en el estudiantado (Akyuz, 2018;Boz y Adnan, 2017;Salas-Rueda et al, 2019;Samaniego et al, 2015). De hecho, el crecimiento acelerado de las herramientas tecnológicas basadas en internet está provocando el surgimiento de nuevos modelos para la enseñanza y el aprendizaje (Nelson et al, 2019;Reyes et al, 2017;Salas-Rueda, 2019;Tibi, 2018). En particular, el aula invertida es un modelo pedagógico que propone la realización de diversas actividades dentro y fuera del salón de clases a través del uso de las TIC (Urbina et al, 2015).…”
Section: Introductionunclassified